Apolar distal pocket mutants of yeast cytochrome c peroxidase: Binding of imidazole, 1-methylimidazole and 4-nitroimidazole to the triAla, triVal, and triLeu variants - Bidwai, Anil (Biochim Biophys Acta, 2015)
Imidazole binding to three apolar distal heme pocket mutants of yeast cytochrome c peroxidase (CcP) has been investigated between pH 4 and 8. The three CcP variants have Arg-48, Trp-51, and His-52 mutated to either all alanine, CcP(triAla), all valine, CcP(triVal), or all leucine residues, CcP(triLeu). The imidazole binding curves for all three mutants are biphasic indicating that each of the mutants exist in at least two conformational states with different affinities for imidazole. At pH 7, the high-affinity conformations of the three CcP mutants bind imidazole between 3.8 and 4.7 orders of magnitude stronger than that of wild-type CcP while the low-affinity conformations have binding affinities about 2.5 orders of magnitude larger than wild-type CcP. Imidazole binding to the three CcP mutants is pH dependent with the strongest binding observed at high pH. Apparent pK(a) values for the transition in binding vary between 5.6 and 7.5 for the high-affinity conformations and between 6.2 and 6.8 for the low-affinity conformations of the CcP triple mutants. The kinetics of imidazole binding are also biphasic. The fast phase of imidazole binding to CcP(triAla) and CcP(triLeu) is linearly dependent on the imidazole concentration while the slow phase is independent of imidazole concentration. Both phases of imidazole binding to CcP(triVal) have a hyperbolic dependence on the imidazole concentration. The apparent association rate constants vary between 30 and 170 M(−1)s(−1) while the apparent dissociation rate constants vary between 0.05 and 0.43 s(−1). The CcP triple mutants have higher binding affinities for 1-methylimidazole and 4-nitroimidazole than does wild-type CcP.